Amendments of Severe Saline-Sodic Paddy Land: Optimal Combination of Phosphogypsum, Farmyard Fertilizer, and Wood Peat - Guokang Duan; Miao Liu; Zhengwei Liang; Mingming Wang; Haoyu Yang; Yang Xu; Tianhe Yu; Yangyang Jin; Jiafeng Hu; Junqing Liu (Agronomy, 2023)
We aimed to determine the optimal combination of amendments to increase rice yields in saline-sodic soil. The effects of different proportions of phosphogypsum (P), farmyard fertilizer (F), and wood peat (W) across the main growth period of rice were studied. A total of 14 treatments were designed based on the “3414” fertilizer effect field experiment scheme, with 3 factors (P, F, and W) and 4 application levels per factor. Application of a combination of P, F, and W reduced soil pH and electrical conductance (EC) (p < 0.05), increasing rice yields. The theoretical rice yield after treatment P2F2W2 (P 30, F 50, and W 30 t·ha−1) was 5819.20 kg·ha−1, which was 32.52-fold higher than that after P0F0W0 (P, F, and W, 0 t·ha−1). Panicle weight, number of total filled grains, total grain weight, and seed-setting rate were 9.76, 17.35, 32.11, and 3.96 times higher than those in the control treatment, respectively. Compared with the control P0F0W0 treatment, soil pH in P2F2W2 in 0–5, 5–10, 10–15, and 15–20 cm depth decreased by 12.69, 12.32, 11.18, and 10.70%, respectively, and soil EC was 1.06-fold, and 70.79, 49.30, and 47.76% higher, respectively. Overall, we found that the P2F2W2 treatment, with a combination of P, 29.09–32.38 t·ha−1; F, 40.36–46.97 t·ha−1; and W, 19.57–23.95 t·ha−1 was optimal in this experiment.